Meta-Analisis : Studi Pentingnya Mengukur Keterampilan Metakognitif Siswa - Hajiriah, Titi Laily; Sudiatmika, AAIA Rai; Suma, I Ketut; Suardana, I Nyoman (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This study aims to find the effect size of several journals that contain articles with uniform topics. The purpose of finding effect size is to measure the extent of differences or relationships between two or more variables or groups in scientific research. Effect size provides information regarding the strength and size of the observed effect, regardless of the sample size used. By evaluating effect size, researchers can determine the practical significance of their findings and compare the results of studies conducted by other researchers. The key word of this meta-analysis study is metacognitive skills. This meta-analysis is important to get an idea of studies that report the results of measuring metacognitive skills at various levels. The research method used in this study is a meta-analysis method with an experimental approach to journal tracking using OpenMEE software with keywords used, namely metacognitive skills, metacognition, metacognition awareness. Based on meta-analysis calculations that there is a relationship between all metacognitive skill measurement articles, a p value of < 0.001 means that the analysis is significant with sig. 0.05 and I^2 above 80% indicate that heterogeneity of learning measures metacognitive skills of 93.985 and the sample effect size in this study is very high heterogeneity.